2017
DOI: 10.3368/jhr.53.2.0816-8112r1
|View full text |Cite
|
Sign up to set email alerts
|

Developing Hope among Impoverished Children

Abstract: The role of psychological attributes such as hope in escaping poverty has attracted increasing attention. Crucial questions include the impact of early development of positive psychological attributes on socioeconomic outcomes, and whether interventions to reduce poverty increase such attributes. We examine the impact of international child sponsorship on the psychology of Indonesian children by employing a novel program evaluation technique—a quantified analysis of children’s self-portraits. To identify causa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…CI youth are also connected to individual, family, or group sponsors who support youth through monthly financial support, personal letters, and in some cases, gifts, and personal visits. 1 CI emphasizes the importance of relationships between youth participants and caring adults (e.g., project directors, pastors, and mentors) (Glewwe et al 2018;Sim and Peters 2014;Tirrell et al 2019a). A recent study suggests that CI-involved youth benefit from this strength-based approach and exhibit significantly higher levels of hope (Glewwe et al 2018).…”
Section: El Salvador and Compassion International (Ci)mentioning
confidence: 99%
See 1 more Smart Citation
“…CI youth are also connected to individual, family, or group sponsors who support youth through monthly financial support, personal letters, and in some cases, gifts, and personal visits. 1 CI emphasizes the importance of relationships between youth participants and caring adults (e.g., project directors, pastors, and mentors) (Glewwe et al 2018;Sim and Peters 2014;Tirrell et al 2019a). A recent study suggests that CI-involved youth benefit from this strength-based approach and exhibit significantly higher levels of hope (Glewwe et al 2018).…”
Section: El Salvador and Compassion International (Ci)mentioning
confidence: 99%
“…1 CI emphasizes the importance of relationships between youth participants and caring adults (e.g., project directors, pastors, and mentors) (Glewwe et al 2018;Sim and Peters 2014;Tirrell et al 2019a). A recent study suggests that CI-involved youth benefit from this strength-based approach and exhibit significantly higher levels of hope (Glewwe et al 2018). The researchers suggested that it is this holistic approach, which operates on the spiritual, psychological, and social fronts, that might be more likely to have positive effects on development, as opposed to economic sponsorship alone.…”
Section: El Salvador and Compassion International (Ci)mentioning
confidence: 99%
“…For example, Chitchai et al (2020) confirmed that hope for money mediated the relationship between socioeconomic status and happiness. Adult hope was based on the development of children’s brain and cognition ( Glewwe et al, 2017 ), which is influenced by childhood socioeconomic status ( Farah et al, 2006 ; Hair et al, 2015 ). Does childhood socioeconomic status affect adult subjective wellbeing through the mediating role of hope?…”
Section: Introductionmentioning
confidence: 99%
“…Taking all aforementioned findings together suggests a need to improve measurement of mental health and detecting possible exposure to extreme traumatic events among adolescent populations. Such work is being undertaken using children’s drawings to measure mental health outcomes and exposure to violence in refugee settings [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%